Municipal solid wastes pyro-gasification using high-temperature flue gas as heating resource and gasifying agent. (15th July 2022) - Ge, Shaoheng; Chen, Dezhen; Yin, Lijie; Hong, Liu; Zhou, Hongquan; Huang, Zhen
Graphical abstract: Highlights: MSW pyro-gasification process with HTFG as heating source and gasifying agent. Roles of CO2, H2 O, and mixture of CO2 /H2 O/O2 in HTFG were investigated. Energy share in the gas products was approximately 75% for model flue gas supply. The residue tar can be used to produce HTFG. The interaction between the char gasification and volatile reforming was explored. Abstract: With the implementation of municipal solid wastes (MSW) source segregation collection policy, the combustible waste components are suitable for pyrolysis treatment to recover value-added energy such as gas or oil. In this research, the volatile compounds from MSW pyrolysis were reformed by the char obtained from the same process and the high-temperature flue gas (HTFG) of 1200 °C was supplying as heating resource and gasifying agent in a tailor-made experimental set-up. The final yields and properties of the syngas, char, and oil after reforming were investigated. Experimental studies showed that the composition of HTFG had a significant influence on the products. As the HTFG being CO2 and its flowrate increased from 0 to 4 L/min/(kgMSW ), the energy share in the gas first increased from 8.29 to 15.1 MJ/(kgMSW ) with a higher heat value (HHV) of 19.9 MJ/Nm 3, then it decreased slightly with a further increase in the flowrate. However, as the HTFG was H2 O or the model flue gas (consisting of CO2, H2 O, O2 and N2 ), the higher flowrate always increased the energy share and cold gasification efficiency (CGE) in the gas products. Both CO2 and H2 O participated the volatiles' reforming reactions and enhanced char gasification; while the volatiles' reforming inhibited char gasification. When the flowrate of the model flue gas increased from 0 to 12.04 L/min/(kgMSW ), the oil and char yields decreased and the CGE increased to more than 75%, which was much higher than that from direct air gasification of MSW; moreover, the gas products had much higher HHVs. This research provides a guidance for producing high-quality syngas from the MSW.